Lack of utility of repeat monitoring of hemoglobin and hematocrit following blunt solid organ injury in children. Issue 6 (December 2015) - Acker, Shannon N.; Petrun, Branden; Partrick, David A.; Roosevelt, Genie E.; Bensard, Denis D.
Abstract : BACKGROUND: Current management protocols for children with blunt solid organ injury to the liver and spleen call for serial monitoring of the child's hemoglobin and hematocrit every 6, 12, or 24 hours, depending on the injury grade. We hypothesized that children who require emergent intervention in the form of laparotomy, angioembolization, or packed red blood cell (PRBC) transfusion because of bleeding from a solid organ injury will have changes in their vital signs that alert the clinician to the need for intervention, making scheduled laboratory evaluation unnecessary. METHODS: We performed a retrospective review of all children admitted to either of two pediatric trauma centers following blunt trauma with any grade liver or spleen injury from January 2009 to December 2013. Data evaluated include a need for intervention, indication for intervention, and timing of intervention. RESULTS: A total of 245 children were admitted with blunt liver or spleen injury. Six patients (2.5%) underwent emergent exploratory laparotomy for hypotension a median of 4 hours after injury (range, 2–4 hours), four of who required splenectomy. No child required laparotomy for delayed bleeding from a solid organ injury. One child (0.4%) underwent angioembolization for blunt splenic injury. Forty-one children (16.7%) received a PRBC transfusion during hospitalization, 32 of whom did not undergo laparotomy or angioembolization. Children who underwent an intervention had a lower nadir hematocrit (median, 22.9 vs. 32.8; p < 0.0001), longer time from injury to nadir hematocrit (median, 35.5 vs. 16 hours; p < 0.0001), and more total blood draws for hemoglobin and hematocrit monitoring (median, 20 vs. 5; p < 0.0001). CONCLUSION: Among children with blunt liver or spleen injury, a need for emergent intervention in the form of laparotomy or PRBC transfusion for hemorrhagic shock occurs within the first 24 hours of injury. Ongoing, scheduled monitoring of serum hemoglobin and hematocrit values may not be necessary. LEVEL OF EVIDENCE: Retrospective study with no negative criteria, prognostic study, level III.